The Overlooked Role of Social Work in Strengthening SMEs for Community Development in South Africa - DIPELA, PERCY (Universitas Nahdlatul Ulama Surabaya, 2025)
Small and medium-sized enterprises (SMEs) are generally seen in South Africa as job creators and local economy developers, but evidence that they turn out so badly indicates that current support arrangements remain insufficient. A lot of literature and policy debate regarding the topic surrounds issues of money, technology, and regulation without any mention of psychosocial and interpersonal challenges that face entrepreneurs on a day-to-day basis. Based on a desktop study design, this research integrates academic literature, policy briefs, and practitioner data to analyze the nexus of SMEs, public–private partnerships (PPPs), and social work in community development. The research indicates that, in spite of entrepreneurs exerting immense psychosocial pressures, these are deliberately left out of SME and PPP strategies that focus deliberately on economic efficiency over social welfare. Informed by the capability approach to development studies and the strengths perspective of social work, the essay's thesis is that SMEs are not merely economic agents but social anchors for life in communities. It advocates an integrated approach where social workers are embedded within PPP projects and SME support initiatives to break down psychosocial barriers, build trust in communities, and promote resilience. Integration of social work into PPP and SME interventions holds promise to enhance enterprise sustainability as well as further broader objectives of social justice, dignity, and inclusive community development.